(untitled) (مجلة العلوم الشاملة, 2024)
Incorporating artificial intelligence (AI) tools in education has revolutionised how students learn. Artificial intelligence )AI (enables customised learning experiences and improves teaching strategies; as a result, teachers can dedicate more time to engaging with students and providing assistance, which can lead to better overall educational results, particularly for English as a Second Language (ESL) students. Despite the benefits of AI tools, this qualitative literature review paper explores the dual impact of AI tools on the development and destruction of essential 21st-century skills, including critical thinking, collaboration, creativity, and communication. On the other hand, notable challenges include over-reliance on technology, reduced interaction and interpersonal communication, and a decline in critical thinking abilities. This study highlights the advantages and challenges of using AI in ESL contexts by reviewing recent literature. The key findings underscore the importance of a balanced approach to integrating AI tools into ESL curricula to optimise educational outcomes. This review synthesises current research and offers actionable recommendations for educators to leverage AI in language learning settings effectively.